«Soviet scholars were on duty»: studying and teaching of the archaeology and the history of primitive society in the Belarusian State University during the war and post-war period - Vaitovich, Aliaksandra U. (Journal of the Belarusian State University. History, 2021)
The article deals with the little-known pages of the history of archaeology and education. It reveals the main aspects of the teaching of archaeology and other disciplines of the relevant profile at the Belarusian State University in the period from 1940s to the beginning of 1950s. Lectures were conducted by full-time staff members of the Belarusian State University. Moscow scholars as well as fellow workers of the Institute of History of the Academy of Sciences of the BSSR were also invited for teaching. Scientific activity in the field of archaeology and closely-related disciplines was constrained by personnel problems and restricted material resources. University intellectuals carried did their best to restore the Museum of history and archaeology, however, due to the lack of exhibition space, the renewed exposition had not been opened.